Ultrasound-Assisted One-Pot Synthesis and Anti-Inflammatory Evaluation of 2,4,5-Trisubstituted Imidazoles with Hemocompatibility Assessment - Hilal, Duaa Abed; Hanoon, Haitham Dalol; Al-Saadi, Narjis Hadi (Indonesian Journal of Chemistry, 2026)
Imidazole derivatives are well known for their anti-inflammatory potential, and recent studies focus on synthesizing 2,4,5-trisubstituted imidazoles through faster, greener methods. In the present study, a series of such derivatives (N1–N10) was prepared in a single-pot, ultrasound-assisted reaction using benzil, various aromatic aldehydes, and ammonium acetate, with sulfuric acid as the catalyst. This procedure shortens reaction times, enhances yields, and reduces waste, offering a greener alternative to conventional heating methods. The products were fully characterized by ¹H-NMR, ¹³C-NMR, FTIR, and MS. Four representative derivatives (N2, N4, N5, and N8) were selected for biological evaluation. Their anti-inflammatory activity was assessed in vitro using trypsin inhibition and albumin denaturation assays, with diclofenac sodium as the reference. N5 and N8 showed potent trypsin inhibition (61.63 ± 1.74 and 53.49 ± 0.45%) comparable to diclofenac (61.69 ± 0.74%), while N2 achieved 60.71 ± 3.68% and N4 50.33 ± 0.58%. In albumin denaturation, N5 and N8 again displayed high activity (76.8 ± 6.3 and 76.55 ± 0.89%), N2 58.33 ± 0.62% and N4 50.33 ± 0.58%. All compounds produced < 5% hemolysis, indicating good hemocompatibility. The findings demonstrate that ultrasound enables a greener and more efficient synthesis of anti-inflammatory imidazole derivatives, while also highlighting these compounds as promising, safe, and effective candidates for future therapeutic development.